The Influence of Digital Competency on Digital Human Resources Transformation of Employees of the Department of Agriculture and Food Security of Karawang - Yulia Nur Fadilah,; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
With the advancement of technology, HR management must consider its impact on HR performance capabilities through employee competencies. This study aims to analyze the influence of employee digital competencies on digital HR transformation in the government sector. This research method uses a quantitative descriptive method. The research locus is the Karawang Regency Agriculture and Food Security Service, which has a population of 98 employees. The sample used was 96 respondents. Data were collected using a questionnaire via Google Forms. Furthermore, the data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 4 tool. The results of the study showed that digital competency had a significant effect on digital HR transformation. The implementation of digital HR transformation showed good results at the Karawang Agriculture and Food Security Service because the digital competencies of employees were already competent in several aspects. This study can be a reference for similar research for further studies, especially in supporting more effective government performance.